Factors Associated with the Incidence of Early Menarche in Young Girls at SMP Negeri 15 Padang in 2022 - Eliza Trisnadewi; Rahma Irlah; Gusliani Eka Putri; Oktariyani Dasril; Fenny Fernando (STIKES Syedza Saintika Padang, 2022)
Data from the Padang City Health Office states that there has been an increase in the incidence of menarche since 2021. The incidence of menarche in 2021 is 50% of adolescents who get menarche under the age of <11 years The fear of early menarche is bleeding. This study aims to determine the factors associated with the incidence of early menarche in adolescent girls at SMP Negeri 15 Padang in 2022. This type of research is analytic with cross sectional design . This research was conducted at SMP Negeri 15 Padang on July 18 to August 8, 2022. The population of this study were all students of class VII, totaling 108 people with a total sample of 90 people. The sampling method used proportional random sampling technique. Data was collected using a questionnaire by means of a questionnaire. Data processing was carried out univariate and bivariate with Chi Square test using SPSS program.Based on the results of the study, it was found that 58,8% of young women experienced early menarche, 32,9% of young women experienced underweight nutritional status, 72,9% experienced a history of early maternal menarche and 61,2% of young women were exposed to mass media. Chi Square test results obtained p value = 0,011 < a = 0,05 (nutritional status), p value = 0,046 < a = 0,05 (mother's menarche history) and p value = 0,008 < a = 0,05 (media exposure mass). Based on the research , it can be concluded that there is a relationship between the history of nutrisional status, maternal menarche and exposure to mass media with the incidence of early menarche. It is hoped that the school can provide counseling about the factors that can cause early menarche.